A mitochondria-targeted colorimetric and two-photon fluorescent probe for biological SO2 derivatives in living cells. (November 2016) - Wang, Qi; Wang, Wenjuan; Li, Shanqing; Jiang, Jun; Li, Daoxue; Feng, Yan; Sheng, Hongting; Meng, Xiangming; Zhu, Manzhou; Wang, Xin
Abstract: Two colorimetric and two-photon fluorescent probes (PCB andMPCB ) for SO2 derivatives were designed and synthesized with rapid response, high selectivity, low detection limits, and large Stokes shifts. The probes displayed "turn on" fluorescence response to SO2 derivatives probably due to the nucleophilic addition to the electron-poor CN bond, which was supported by the DFT/TDDFT calculations. Compared withPCB, MPCB was obtained by incorporating a methyl pyridinium group, which endowedMPCB with the red-shifted spectra properties, better water-solubility, larger two-photon excitation action cross-section ( δ ′) and the important ability of locating in mitochondria. Bio-imaging study established thatMPCB can be used to detect SO2 derivatives in living cells under two-photon excitation with large δ ′ value (1551 × 0.125 = 193.88 GM), little cytotoxicity and good biocompatibility. Meanwhile, standard co-staining experiments ofMPCB and Mito Tracker Red FM (co-localization coefficient: 0.89) revealed thatMPCB can be used for the real-time sensing and bioimaging of SO2 derivatives in mitochondria. Graphical abstract: A mitochondria-targeted colorimetric and two-photon fluorescent probe (MPCB ) was developed for highly selective detection of SO2 derivatives and bio-imaging in mitochondria under two-photon excitation. Highlights: MPCB showed a colorimetric and fluorescence "turn-on" response for SO2 derivatives. MPCB can be used to detect SO2 derivatives in living cells under two-photon excitation. MPCB can be predominantly present in mitochondria with a co-localization coefficient of 0.89.